'Municipal entrepreneurs': local politicians and the delivery of urban sanitation in Kumasi, Ghana. Issue 2 (2nd April 2020) - Sabbi, Matthew
ABSTRACT: The municipal government in Kumasi has been the focus of numerous reforms to improve local policymaking and delivery of public goods to the city's dwellers. Yet, the reforms have spurred strategic reactions from local actors who exploit institutional ambiguities to pursue their interests. This paper draws on empirical data on the city's sanitation franchising to show how ordinary local politicians exploit reform ambiguities; they establish themselves as local entrepreneurs to deliver urban sanitation services and also contest the municipal executive. The manipulations do not only undermine reforms proffered by the regime and external actors but the municipal government's promise to deliver efficient public services also becomes problematic. Management of urban sanitation is a contested arena between bureaucrats and political actors all vying for their interests. The sanitation reforms are eventually subsumed under the 'local politics as usual' logic.